Large resistivity in numerical simulations of radially self-similar outflows - Čemeljić, Miljenko; Vlahakis, Nektarios; Tsinganos, Kanaris (2011)
We investigate conditions in a radially self-similar outflow in the regime of large resistivity. Using the PLUTO code, we performed simulations with proper choice of boundary conditions, relaxed at the footpoints of critical surfaces in the flow. We investigate outflow propagation in a high-resistive disk corona, and compare it to the results with small or vanishing resistivity.
Keywords: magnetic fields (magnetohydrodynamics): MHD; methods: numerical; outflows; stars: winds